Секретный агент: [роман] / Александр Тамоников - Тамоников Александр Александрович (Спецназ, 2007)
Экземпляры: ф.6 (20171211) / Инвентарный номер: 2251 / Цена: / Сис.шифр: 84(2рос=Рус)6-4 / Авт.знак: Т 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44